2015
DOI: 10.26858/est.v1i3.1824
|View full text |Cite
|
Sign up to set email alerts
|

Revitalisasi Nilai Etos Kerja Dalam Hadih Maja Sebagai Bahan Ajar Pendidikan Karakter

Abstract: This study aimed to identify and interpret the basic principles and characteristics of values ofHadih maja merupakan puisi lisan Aceh yang identik dengan ungkapan tradisional atau puisi rakyat (Harun, 2006) sebagaimana juga dimaksudkan Brunvand (1968:38) dan Danandjaja (1997:21-22) tentang puisi lisan. Hadih maja sering juga diartikan sebagai kata atau kalimat berhikmat (Hasjmy dalam Ara, dkk., 1995:539) atau nasihat dan petuah hidup nenek

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Integrity, morality, moral rectitude, moral fortitude, moral tenacity, and tenacity are all facets of a person's ethos. Thus, ethos can be thought of as the way of life shared by a particular social group, while work ethic is the dedication to one's craft that serves as a defining characteristic and set of beliefs (Mohammad Harun, Husaini Ibrahim, 2015).…”
Section: A Historical Portrait Of the Work Ethos Of Acehnese Women In...mentioning
confidence: 99%
“…Integrity, morality, moral rectitude, moral fortitude, moral tenacity, and tenacity are all facets of a person's ethos. Thus, ethos can be thought of as the way of life shared by a particular social group, while work ethic is the dedication to one's craft that serves as a defining characteristic and set of beliefs (Mohammad Harun, Husaini Ibrahim, 2015).…”
Section: A Historical Portrait Of the Work Ethos Of Acehnese Women In...mentioning
confidence: 99%
“…It has been demonstrated that peurateb aneuk can shape the character of the Aceh community. The main characteristics that stand out the most are consistency, optimism, and religion, 13 but changing times have caused the loss of aneuk peurateb. A type of recorder or cell phone replaced this activity, causing a shift in values and good practices toward children.…”
Section: Introductionmentioning
confidence: 99%
“…Hadih maja is Aceh's oral poetry that is synonymous with traditional expressions or folk poetry (Mohd. Harun, 2006;Herman, Mukhlis, Saiful, & Sanusi, 2018). In daily life, Acehnese proverbs are used to improve work ethic.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the means of expression in various communication contexts to convey the intention of the speaker. Third, as a directive function (Mohammad Harun, Qismullah Yusuf, & Karnafi, 2020;Mohd. Harun, 2006).…”
Section: Introductionmentioning
confidence: 99%